Radicalized loyalties becoming Muslim in the West - Truong, Fabien (Polity Press, 2018)
There is widespread concern today about the "radicalization" of young muslim men, and the deprived areas of Western cities are believed to have become breeding grounds of home-grown extremism. Becoming Muslim does not necessarily lead to the radicalized "other." It is more like a long-distance race, a powerful reconversion of the self that allows for introspection and change. But it can also lead to a belligerent presentation of the self that transforms a dead-end into a call to arms.